Preliminary development of microwave incinerator (labarotary scale) of liquid organic waste - Izzati Ismail (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This project involves a preliminary study todispose of organic waste. It uses microwaves to dispose of organic waste in liquid from. Previously fond that blood,especially liquid waste wiil be disposed of on-site disposal. Liquid waste will be collected by a athortity to dispose and should be taken out of the linic. Therefore, this project is to make a preliminary study on the microwave using a laboratory scale.